2016
DOI: 10.1093/europace/euv412
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of left atrial appendage closure with the Watchman device for atrial fibrillation patients with absolute contraindications to warfarin

Abstract: AimsAtrial fibrillation (AF) patients with contraindications to oral anticoagulation have had few options for stroke prevention. Recently, a novel oral anticoagulant, apixaban, and percutaneous left atrial appendage closure (LAAC) have emerged as safe and effective therapies for stroke risk reduction in these patients. This analysis assessed the cost effectiveness of LAAC with the Watchman device relative to apixaban and aspirin therapy in patients with non-valvular AF and contraindications to warfarin therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 36 publications
0
29
1
Order By: Relevance
“…11 Interestingly, the economics of LAA occlusion therapy using the Watchman device relative to both warfarin and novel oral anticoagulants (NOACs) has been the subject of several prior economic analyses. [12][13][14] When examining model-based economic analyses of medical care involving chronic disease therapies (such as AF), 2 points are worth keeping in mind. First, before considering any cost data, attention should be directed to the clinical effectiveness story reflected in the model and how that relates to the understanding of effectiveness based on empirical trial data.…”
Section: See Article By Freeman Et Almentioning
confidence: 99%
“…11 Interestingly, the economics of LAA occlusion therapy using the Watchman device relative to both warfarin and novel oral anticoagulants (NOACs) has been the subject of several prior economic analyses. [12][13][14] When examining model-based economic analyses of medical care involving chronic disease therapies (such as AF), 2 points are worth keeping in mind. First, before considering any cost data, attention should be directed to the clinical effectiveness story reflected in the model and how that relates to the understanding of effectiveness based on empirical trial data.…”
Section: See Article By Freeman Et Almentioning
confidence: 99%
“…However, it should be the weaker argument against LAAC. Different studies have demonstrated the cost-effectiveness of the LAAC procedure for NVAF [2,3,15]. What's more, all of them have demonstrated its superiority over the NOACs.…”
Section: Price / Reimbursement Issuesmentioning
confidence: 99%
“…The ICER per QALY gained of LAAC over warfarin has been calculated as low as $3,432 [15]. A very interesting study [3] e) The same group of investigators performed a similar analysis [2] in patients with absolute contraindications to warfarin. The selected comparators for the LAAC were aspirin plus clopidogrel [18] and apixaban [14].…”
Section: Price / Reimbursement Issuesmentioning
confidence: 99%
“…LAA closure is associated with an upfront procedural cost that is offset later due to the absence of the cost of oral AC therapy and associated complications. 13 Recently, Panikker et al 58 published a cost-impact analysis from randomized clinical trial studies and real-world experience comparing the cost of LAA closure using the WATCHMANt (Boston Scientific) with available oral anticoagulants. The study showed that LAA closure with the WATCHMANt (Boston Scientific) in a real-world setting may result in lower stroke and major bleeding rates than that reported in clinical trials.…”
Section: Cost Effectiveness Of Left Atrial Appendage Closurementioning
confidence: 99%
“…Some studies have suggested that this approach may be cost effective in the long run when compared with long-term AC. 12,13 LAA exclusion therapies are evolving. Improvements in device design and increasing operator experience have significantly improved the procedural safety profile of LAA exclusion devices.…”
Section: Introductionmentioning
confidence: 99%